Caloric content of the sand fly Lutzomyia ovallesi (Diptera: Psychodidae) vector of Leishmania - NOGUERA, PEDRO; RONDON, MARITZA; NIEVES, ELSA (Revista Colombiana de Entomología, 2006)
Females of the sand fly Lutzomyia ovallesi (Ortiz) (Diptera: Psychodidae) were fed with blood from various species of vertebrates and analyzed to determine energy reserves under laboratory conditions. L. ovallesi specimens were allowed to artificially feed to satiation through chicken membranes on blood from horse, dog, cow, chicken, goat, pig or human. Caloric reserves were calculated spectrophotometrically after females were homogenized in a solution of sodium dichromate and sulfuric acid. The caloric content of L. ovallesi varied according to the type of vertebrate blood on which it had fed. The highest content (cal/insect) was found in females fed on human blood (0.33), followed in decreasing order by dog, pig, cow, chicken, goat and horse (0.26). Statistical analysis showed significant differences (P < 0.05) among sources. The results showed that human and dog blood meals were more nutritionally efficient. The most inefficient diet for L. ovallesi was horse blood manifested by its poor nutritional quality.